PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PELATIHAN TAS ANYAM DI DUSUN KLIYUR DESA DAYAKAN - Maya Asri Adistalaili (Journal of Islamic Science Community, 2022)
The economy isanimportantelementin thesociety. The community's economy is one of the things to pay attention to, because the success of a societyis when the communityisabletofulfilalltheirneeds, even the economy is one of the problems that is widely discussed to find a solution. In oneofthe villages in Ponorogo, namely Dayakan village, especially the Kliyur hamlet as one of the villages with limitations ineconomicvalue,itisdifficult to develop the capacity of the community itself whose people havelowincomesasthemajorityof the people focus on the income of the land they manage. Gradually the Indonesian people in urban areas have developed a more advanced lifestyle which without realizing it has an impact on rural communities. One way to overcome community problems like this is by empowering the community. Community empowerment is a development concept with community values ​​to build a community paradigm in helping the economy of the community in the village. One of the things that has been done in Kliyur hamlet in empowering the community is by holding woven bag training which can be used as a source of livelihood.